Method of Teaching Large form on the Example of Symphony and Oratorio by Russian Composers in Art Schools - Okhunjon Kimsanov; Firdavs Erkinov (Bright Mind Publishing, 2025)
The teaching methodology of large-scale musical forms, such as symphonies and oratorios by Russian composers, plays a crucial role in shaping students’ understanding of musical structure, thematic development, and artistic expression. These compositions, exemplified by the works of P. I. Tchaikovsky, S. V. Rachmaninoff, D. D. Shostakovich, and S. S. Prokofiev, provide a foundation for studying orchestration, form, and the interaction between vocal and instrumental elements. In music schools, the challenge lies in developing pedagogical strategies that enable students to analyze and perform these complex works while enhancing their technical and interpretative skills. Effective teaching methods include structural analysis, guided listening, performance-based learning, and historical contextualization. In Uzbekistan, Russian symphonies and oratorios remain an integral part of the curriculum, offering students an opportunity to engage with the depth and richness of large-scale compositions. This article explores the methodology for teaching symphonies and oratorios in music schools, their pedagogical significance, and their impact on students' musical development.
Keywords: Large-scale forms, symphonies, oratorios, Russian composers, music education, teaching methodology, structural analysis, orchestration, historical context, performance practice.